Differentially enriched fungal communities in root rot resistant and susceptible varieties of tobacco (Nicotiana tabacum L.) under continuous monoculture cropping - Ao, Jincheng; Wang, Zheng; Yang, Qigang; Li, Bo; Li, Ying; Li, Yongmei (Frontiers in Microbiology, 2022)
Root rot is a major disease of tobacco that causes crop losses of up to 15–20% of global tobacco production. The present study aimed to compare the fungal communities, and physicochemical properties of rhizosphere soil of root rot resistant (Yunyan 87; Y) and susceptible (Honghua Dajinyuan; H) tobacco varieties. Four treatments of each variety under continuous monocropping cultures included: control groups (HT0 and YT0); 2 years of continuous cropping (HT2 and YT2); 4 years of continuous cropping (HT4 and YT4); and 8 years of continuous cropping (YT8 and HT8). The soil physicochemical properties including available nitrogen (AN), available phosphorus (AP), available potassium (AK), and organic matter (OM) were increased (p < 0.05) from HT0 to HT8, whereas the resistant variety (Y) showed an inconsistent trend from YT0 to YT8. The pH was decreased (p < 0.05) from HT0 to HT8 and YT0 to YT8. Further, the disease incidence rate and disease index of the H variety also increased (p < 0.05) from HT0 to HT8. Alpha diversity analysis revealed that susceptible variety had higher fungal diversity from HT0 to HT8, while resistant variety exhibited lower diversity from YT0 to YT8. Ascomycota and Mortierellomycota were the dominant phyla in H and Y. Ascomycota abundance was increased (p < 0.05), whereas Mortierellomycota was decreased (p < 0.05) for continuous cropping years in H and Y. Penicillium, Fusarium, and Chrysosporium were the top three abundant genera in both varieties. The relative abundance of Penicillium spp. was increased (p < 0.05) in Y, whereas decreased (p < 0.05) in H variety. Specifically, Chrysosporium spp. was increased (p < 0.05) whereas Fusarium spp. was decreased (p < 0.05) in YT2. Redundancy analysis (RDA) revealed that fungal communities in H and Y rhizospheres were influenced by pH and carbon content, respectively. The top three highly enriched (p < 0.05) pathways in both varieties were fatty acid elongation, fatty acid β-oxidation I, and glyoxylate cycle. Our study concluded that resistant variety exhibited lower fungal diversity and functionally enriched metabolic pathways than susceptible variety that might be the result of molecular breeding practices, however, the relative abundance of Penicillium spp. were increased in resistant variety under long-term monoculture cropping.